Empowering the Next Generation: The Naleemiah Institute of Islamic Studies and Its Impact on Muslim Youth Leadership - Mohamed Arkam Mohamed Rasak (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study explores the transformative role of the Naleemiah Institute of Islamic Studies (NIIS) on Muslim youth leadership in Sri Lanka, examining how its educational model fosters intellectual, ethical, and social development. The primary objective is to assess how NIIS equips young Muslims with the knowledge, skills, and values necessary for effective leadership in a multicultural society. Additionally, the study investigates the institute’s role in promoting inclusivity, critical thinking, and civic engagement among its students. Adopting a descriptive-analytical approach, this research draws on scholarly literature and institutional documents to assess NIIS’s curriculum, pedagogical strategies, and community initiatives. The findings indicate that the institute’s balanced education system, merging Islamic principles with modern disciplines, strengthens students’ intellectual and moral development, preparing them to navigate global challenges while preserving religious identity. Furthermore, NIIS’s emphasis on community services, leadership training, nd interreligious engagement reinforces a sense of social responsibility, empowering youth to contribute positively to national development. The study concludes that NIIS serves as a critical institution for empowering the next youth generation, bridging tradition and modernity to produce religiously grounded and globally competent leaders. The institutional role in Sri Lanka’s social-cultural progress is to nurture ethical leadership and active citizenship.